PERANAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA ANGGOTA KEPOLISIAN PADA POLSEK ILIR TIMUR II KOTA PALEMBANG - Reni Juliati; Nifi Lamingthon (STIA SATYA NEGARA PALEMBANG, 2022)
A leader must be trustworthy and must be able to communicate his vision; meaning that he must be able to transform his vision to members, the values he holds as well as his integrity and belief. As is the case with other instruments of state power, the Indonesian National Police is a revolutionary tool in the framework of the Universal National Development Plan towards achieving a just and prosperous society together based on Pancasila or the Indonesian Socialist society in order to fulfill the Mandate of People's Suffering.The purpose of writing this research is to determine the role of a leader in improving the performance of police officers at the Ilir Timur II Palembang Police and to determine the factors that hinder the role of leadership in improving the performance of police officers at the Ilir Timur II Palembang Police. This study uses a qualitative descriptive analysis technique with an evaluative method, which is summative because it is carried out after the program is implemented.The results of the research from data through interviews, it was found that the leadership role was quite good but still needed improvement. Ability improvement orientation focuses on developing skills and employee performance needs to be managed properly to achieve organizational goals, the Police Chief must be able to carry out his role to increase his involvement and power towards members and must apply varied leadership styles, which are appropriate and in line with the maturity level of employees as subordinates, in carrying out a job task that is the authority and responsibility of members of the police force.Contribute to increasing the work productivity of its members and be able to influence subordinates, recognize the characteristics of subordinates, diagnose situations, make decisions, be able to master communication techniques, be able to be participative, be able to establish good relationships with subordinates, be able to provide assessments and give awards. Keywords: leadership, performance